The Role of Online Search Attention in Enhancing Environmental Impact on Financial Performance - Hanum, Atika Violeta; Makaryanawati; Andayani, Endang Sri (Jurnal Mebis, 2025)
This study examines the influence of environmental performance on financial performance, with a focus on the moderating role of online search attention, using a sample of Indonesian State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange in the 2021–2024 period. Data were collected from sustainability reports, financial statements, and Google Trends. A pilot study approach in moderated regression analysis was used to accommodate manifest variables and evaluate interaction effects between variables. The results indicated that environmental performance positively contributed to improved financial performance. Furthermore, online search attention strengthened the relationship between environmental performance and financial performance. The effect of environmental performance on financial performance after moderating variables was highly significant. This indicates that public interest strengthens the financial benefits of environmental practices. These findings highlight the strategic importance of both environmental responsibility and digital visibility in enhancing firm value. This study contributes to the ESG literature by integrating the role of online public attention and offers managerial implications for improving environmental communication and stakeholder engagement in achieving sustainable financial outcomes.